Pelatihan Terjemah Al Qur-An Per Kata Sistem 8 Jam Pada Ikatan Pendidik Imtaq (IPdI) Orkab Jombang - Moch. Sya'roni Hasan; Mar'atul Azizah; Muhammad Anas Ma’arif; Ari Kartiko; Mihmidaty Ya'cub (An Naf'ah: Jurnal Pengabdian Masyarakat, 2023)
The eight-hour system of the Orkab Jombang Educational Association (IPdI) is an educational approach aimed at deepening the understanding of the teachings of the Qur'an and applying them in everyday life. This article outlines the approaches, methods, and results that can be achieved through this training. The verse-by-word analysis approach becomes the primary foundation for helping participants understand the meaning of the Qur'an in depth. Thus, the participants were directed to reflect on the meaning of each word in a sentence, translate it into the context of modern life, and apply it in real life. This article describes the steps from the pre-training stage to the implementation of training sessions. Interactive methods and group discussions become pillars for supporting collective understanding and stimulating personal reflection. The training results included an in-depth understanding of the Qur'an, the participants' ability to translate the meaning of the verse contextually, positive changes in views and attitudes, and increased spiritual awareness. This training also has the potential to form a strong character and good ethics, as well as to have a positive impact on society through the translation of sacred teachings into real action. This word-by-word translation training has the potential to enrich religious understanding, form more conscious individuals, and create harmonious and cultural societies. This article emphasizes the importance of an in-depth understanding of the Qur'an and uses it as a guide in dealing with the challenges of modern life.